Determinants Of Satisfaction And Its Implications On Final Semester Economics Faculty Student Loyalty at Private University In DKI Jakarta - Melani Quintania; Yudi Yulius; Nandan Limakrisma; Anoesyirwan Moeins (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this research is to determine methods to promote student loyalty at private universities in DKI Jakarta. The research’s goal is to discover and assess the effects of partial and simultaneous digitalization of learning, service quality, institutional image and student satisfaction toward student loyalty at private universities in DKI Jakarta. Another finding from the research's findings is that student satisfaction acts as a full mediating variable in mediating the variables of digitalization of learning, service quality, and institutional image in increasing student loyalty at private universities in the DKI Jakarta area. To increase student loyalty, the research suggests that priority attention be focused on maintaining the high variable of student satisfaction, namely on the dimensions of satisfaction on the curriculum, namely the suitability of the curriculum with the needs of the world of work, the suitability of courses with the concentration of study programs, and the suitability of the curriculum that keeps up with the timescators who are not interested in moving campuses.